Do diabetes mellitus patients adhere to self-monitoring of blood glucose (SMBG) and is this associated with glycemic control? Experiences from a SMBG program in western Kenya. (February 2016) - Wambui Charity, K.; Kumar, Ajay M.V.; Hinderaker, Sven Gudmund; Chinnakali, Palanivel; Pastakia, Sonak D.; Kamano, Jemimah
Highlights: We assessed the level of non-adherence to SMBG in a SMBG program in western Kenya. We assessed the factors associated with non-adherence to SMBG. We assessed the association between non adherence to SMBG and glycaemic control. Adherence to SMBG was below 80% and was not associated with glycaemic control. Abstract: Aims: Among diabetes mellitus (DM) patients with poor glycemic control enrolled into a self-monitoring of blood glucose (SMBG) program in Kenya, to assess the level of SMBG adherence, its associated factors and its relation to glycemic control (defined as HbA1c <7% and/or 2% absolute reduction relative to baseline). Methods: In this retrospective cohort study, we used routinely collected data of patients enrolled during 2012–2013. We assessed adherence to SMBG by dividing the number of glucose tests performed by the number recommended. A level of ≥80% was considered 'good adherence'. Glycemic control was considered as absolute change from baseline of 2%. Results: Of 164 patients (59% female; 76% rural), the proportions with good SMBG adherence were 34%, 17%, 15% and 10% during 0–6, 7–12, 13–18 and 19–24 months into the HGM program respectively. In multivariate analysis, male gender, urban place of residence and payment for glucostrips were associated with poor adherence during 0–12 months. The mean reduction in HbA1c compared to baseline was 1.2%, 1.1%, 0.8% and 0.7% at 6, 12, 18 and 24 months, respectively. We did not find any association between SMBG adherence and glycemic control. Conclusions: Adherence to SMBG was sub-optimal, especially among those who had to pay for glucostrips. Patient education and provision of free glucostrips are recommended to improve adherence and glycemic control.